Composição fitoquímica dos óleos essenciais de folhas de Lippia alba (Mill.)N.E.Br. em diferentes épocas de colheita e partes do ramo - Castro, D. M. [UNESP]; Ming, Lin Chau [UNESP]; Marques, Marcia Ortiz Mayo [UNESP] (My University, 2002)
This work aimed to determine the best harvest time for biomass production, yield and essential oil composition considering the seasonal variation (spring, summer, autumn and winter) on different plant parts (apical, medial and basal). Essential oils were extracted by hydro-distillation with a Clevenger apparatus for both fresh and dry mass obtained in field and lab conditions respectively. The extracted essential oils were analyzed by GS/MS (Shimadzu, QP-5000). The chemical components were identified by comparing their mass spectrum to the patterns filed in the MS computer memory (Wiley,139,Lib.), to the literature references, and by co-injection with authentic standards. Applying phyto-chemical tests on fresh and dry mass, the chemical component percentages of essential oils were calculated and identified as follows: citral (neral and geranial), myrcene, caryophylene and elemene.
Chemical composition of the essential oils of Lippia alba(Mill.)N.E.Br. at different times of harvest and different parts of branches
Keywords: Lippia alba; Plant components; Volatile oil; beta elemene; caryophyllene; citral; elemene; essential oil; humulene; limonene; linalool; Lippia alba extract; myrcene; nerol; nerolidol; unclassified drug; vegetable oil; zingerone; biomass; chemical composition; drug isolation; gas chromatography; harvest period; mass spectrometer; mass spectrometry; nonhuman; plant stem; seasonal variation